Impact of training and case manager support for traditional birth attendants in the linkage of care among HIV-positive pregnant women in Southwest Nigeria: a 3-arm cluster randomized control trial - Adedoyin O. Ogunyemi; Kofoworola A. Odeyemi; Babasola O. Okusanya; Gbenga Olorunfemi; Melissa Simon; Mobolanle R. Balogun; Alani S. Akanmu (BMC Pregnancy and Childbirth, 2024)
Abstract Background Mother-to-child transmission (MTCT) accounts for 90% of all new paediatric HIV infections in Nigeria and for approximately 30% of the global burden. This study aimed to determine the effectiveness of a training model that incorporated case managers working closely with traditional birth attendants (TBAs) to ensure linkage to care for HIV-positive pregnant women. Methods This study was a 3-arm parallel design cluster randomized controlled trial in Ifo and Ado-Odo Ota, Ogun State, Nigeria. The study employed a random sampling technique to allocate three distinct TBA associations as clusters. Cluster 1 received training exclusively; Cluster 2 underwent training in addition to the utilization of case managers, and Cluster 3 served as a control group. In total, 240 TBAs were enrolled in the study, with 80 participants in each of the intervention and control groups. and were followed up for a duration of 6 months. We employed a one-way analysis of variance (ANOVA) statistical test to evaluate the differences between baseline and endline HIV knowledge scores and PMTCT practices. Additionally, bivariate analysis using the chi-square test was used to investigate linkage to care. Furthermore, logistic regression analysis was utilized to identify TBA characteristics associated with various PMTCT interventions, including the receipt of HIV test results and repeat testing at term for HIV-negative pregnant women. The data analysis was performed using Stata version 16.1.877, and we considered results statistically significant when p values were less than 0.05. Results At the end of this study, there were improvements in the TBAs’ HIV and PMTCT-related knowledge within the intervention groups, however, it did not reach statistical significance (p > 0.05). The referral of pregnant clients for HIV testing was highest (93.5%) within cluster 2 TBAs, who received both PMTCT training and case manager support (p ≤ 0.001). The likelihood of HIV-negative pregnant women at term repeating an HIV test was approximately 4.1 times higher when referred by TBAs in cluster 1 (AOR = 4.14; 95% CI [2.82–5.99]) compared to those in the control group and 1.9 times in cluster 2 (AOR = 1.93; 95% CI [1.3–2.89]) compared to the control group. Additionally, older TBAs (OR = 1.62; 95% CI [1.26–2.1]) and TBAs with more years of experience in their practice (OR = 1.45; 95% CI [1.09–1.93]) were more likely to encourage retesting among HIV-negative women at term. Conclusions The combination of case managers and PMTCT training was more effective than training alone for TBAs in facilitating the linkage to care of HIV-positive pregnant women, although this effect did not reach statistical significance. Larger-scale studies to further investigate the benefits of case manager support in facilitating the linkage to care for PMTCT of HIV are recommended. Trial registration The study was retrospectively registered in the Pan African Clinical Trial Registry, and it was assigned the unique identification number PACTR202206622552114.